The Role of Class Teachers in Implementing Guidance and Counseling Services in Elementary Schools - Srirahmawati, Ija; Putra, Angga; Taufik, Taufik; Puspitasari, Anggun (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study is to determine the implementation of guidance and counseling in elementary schools in the form of assistance provided by teachers to students both individually and in groups to optimize the talents and interests of students and prevent and deal with problems that can hinder the achievement of learning goals. The provision of guidance and counseling in schools is motivated by five things, namely (1) individual development problems; (2) problems of individual differences; (3) problems of individual needs; (4) adjustment problems and behavioral disorders and (5) learning problems. The research method used is descriptive qualitative. The research was conducted at SDN 25 Dompu. Data collection techniques include interviews, observations and documentation. Data analysis techniques include four main stages, namely data collection, data reduction, data presentation and conclusions. The results showed that teachers play a role as implementers of guidance and counseling in elementary schools. There are 5 groups of problems experienced by students at SDN 25 Dompu, namely learning problems, personal problems, social problems, behavioral problems, and career development. The factors causing the problem are motivated by differences in student characteristics, differences in student abilities and differences in students' emotional maturity. The steps in handling student problems are carried out through the stages of identifying problems, collecting data, identifying the cause of the problem, prognosis, namely determining solutions, providing assistance or guidance, and finally conducting evaluation and follow-up. The implementation of guidance and counseling at SDN 25 Dompu has been carried out by all class teachers and school principals.